2018
DOI: 10.20944/preprints201812.0347.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haptic Glove and Platform with Gestural Control for Neuromorphic Tactile Sensory Feedback in Medical Telepresence

Abstract: The advancements in the study of the human sense of touch are fueling the field of haptics. This is paving the way for augmenting the sensory perception during objects palpation in tele-surgery, and reproducing the information through tactile feedback. Here, we present a novel tele-palpation apparatus that enables the user to detect nodules with various distinct stiffness buried in an ad-hoc polymeric phantom. The contact force measured by the platform was encoded using a neuromorphic model and reproduced on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…More broadly, recent studies around telepresence and telepresence robots have shown their potential in clinical settings. 26 , 27 Advances in those areas allied with advances in the field of haptics, 28 , 29 may help to address the unmet need around tactile interaction between patients and families, identified above—this warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, recent studies around telepresence and telepresence robots have shown their potential in clinical settings. 26 , 27 Advances in those areas allied with advances in the field of haptics, 28 , 29 may help to address the unmet need around tactile interaction between patients and families, identified above—this warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, tactile gloves are inextricably linked to the virtual reality interactive simulation system, no matter how powerful they are (34). As an important medium for people to experience the Metaverse, the continuous development of tactile gloves can not only provide a more realistic touch for everyone who experiences the metaverse, but more importantly, it will lay a solid foundation for the future application of the Metaverse in the field of gastroenterology (35). It can be said that only when haptic gloves achieve more accurate feedback and lower latency can virtual endoscopic training and even future remote endoscopic surgery truly achieve truly ideal results.…”
Section: The Tactile Glove Helped Us 'Touch' the Metaversementioning
confidence: 99%